Digitisation of Classical Exercise Practices with STACK: Management of Large Mathematics Classes in Higher Education Institutions - Amour, Idrissa S.; Simba, Fatuma; Kitta, Septimi; Abdalla, Abdi T. (Tanzania Journal of Science, 2023)
Management of large classes’ tutorials is a known problem in Mathematics. Engineering mathematics classes enrol around 1000 students at the University of Dar es Salaam. For effective learning, each tutorial session should register not more than 40 students. This requires at least 25 sessions of tutorials per week, which may not be feasible due to both scarce human resources and venues. In this work, we developed online Mathematics exercises based on the System for Teaching and Assessment using Computer Algebra Kernel (STACK). About 300 STACK questions in linear algebra, calculus, complex numbers, and numerical analysis were constructed for weekly tutorials and quizzes. Students were given an unlimited number of attempts in tutorials and only one attempt for quizzes. The quality of the questions was analysed by examining their facility indices and discriminative efficiencies. Majority of the questions (87%) were within acceptable region. The questions, therefore, provided reasonable insight as appropriate alternative to classical practice. Competent authoring of STACK questions can improve the quality of teaching and learning of Mathematics and save scarce human and material resources required to serve large classes. This can also address the issue of running online programmes in Mathematics and computational subjects to support distance learning.